Was Henry David Thoreau a Good Naturalist? An Approach for Assessing Data from Historical Natural History Records. (24th August 2022) - Primack, Richard B; Miller-Rushing, Abraham J; Miller, Tara K
Abstract: Ecologists are increasingly combining historical observations made by naturalists with modern observations to detect the ecological effects of climate change. This use of historical observations raises the following question: How do we know that historical data are appropriate to use to answer current ecological questions? In the present article, we address this question for environmental philosopher Henry David Thoreau, author of Walden . Should we trust his observations? We qualitatively and quantitatively evaluate Thoreau's observations using a three-step framework: We assess the rigor, accuracy, and utility of his observations to investigate changes in plants and animals over time. We conclude that Thoreau was an accurate observer of nature and a reliable scientist. More importantly, we describe how this simple three-step approach could be used to assess the accuracy of other scientists and naturalists.